Educação financeira nas séries iniciais do ensino fundamental - CRUZ, Ethianne Trindade da (2023)
The present work aims to show the importance of the financial education theme in the initial grades, because during the development of the work and the research carried out, it was possible to observe that this subject is still little addressed in schools. Taking into account that children need to be financially educated from an early age, so that in this way they can be more aware citizens and committed to the future. In view of the above, the concepts of financial mathematics and financial education were addressed, emphasizing that the theme needs to be worked on not only in schools but also in society, since nowadays it is possible to observe that the vast majority of people do not knows how to deal with their financial needs, this happens due to several factors, among them the lack of organization and knowledge. With the development of the article it is also proposed some activities in which there is the possibility of being worked in schools. And finally, a small questionnaire was carried out aimed at the representatives of five schools in the initial series of the urban area of the municipality of Acará, in order to verify if the theme has already been worked on in schools. In view of the reports analyzed, it was possible to observe that financial education in the municipality is not yet in evidence, but when the representatives spoke about the subject, there was a notorious interest in having it inserted, due to the relevance that the subject has in life. of people.